Complications and Pitfalls after Finger Replantation in Young Children - Lafosse, Thibault; Jehanno, Pascal; Fitoussi, Frank (Journal of Hand and Microsurgery, 2018)
Study Design This is a retrospective cohort study.Objective The authors report surgical outcome in a series of very young children who underwent finger replantation after traumatic amputation.Methods During a 10-year period, 65 children were treated with replantation for finger amputation in two institutions. This study focused on replantation of 15 fingers in 13 young patients under 6 years of age (mean age: 2.9 years; range: 1.1–5.7 years). Early postoperative complications were categorized into major or minor. At the time of assessment, the authors evaluated everyday life activities, pain and cold tolerance, total active range of motion (TAM) in patients with successful replantation, and growth disturbance.Results The overall success rate for children younger than 6 years was 47% (7 out of 15), and the authors had 67% of major complications, mainly in patients with crush injuries. There was venous ischemia in 13 (86%) fingers treated with controlled bleeding. The hemoglobin level decreased more than 2 g/dL in six patients, and blood transfusion was necessary in two patients. At the last follow-up, patients with successful replantation had a mean TAM of 72%.Conclusion Despite numerous complications mainly in relation with venous congestion, the functional outcome is satisfactory after successful replantation in young children, which should always be attempted.Level of Evidence/Type of Study Level III, case series, therapeutic study.
Keywords: finger replantation; children; venous congestion; digital amputation; revascularization